Erosive wear of unidirectional carbon fibre reinforced polyetherimide composite - Arjula S.; Harsha A.P.; Ghosh M.K. (My University, 2025)
Solid Particle erosion behaviour of polyetherimide (PEI) and unidirectional carbon fibre reinforced PEI (CF/PEI) has been evaluated using silica sand particles (200 ± 50 μm) as an erodent at different impact angles (15-90°) and impact velocities (25-66 m/s). The influence of fibre orientation (0°- and 90°-orientation) on erosion rate of CF/PEI composite has also been studied. The neat PEI has exhibited maximum erosion rate at 30° impact angle whereas the CF/PEI composite showed maximum erosion rate at 60° impact angle. The results showed that the fibre orientation has a significant influence on erosion rate at oblique impact angles. The erosion rate is higher in the case of 90°-orientation than that of 0°-orientation of fibres. The eroded surfaces were observed under scanning electron microscope to understand the erosion mechanisms. © 2008 Elsevier B.V. All rights reserved.